Metadiscourse in the Arabic Language Text Books of Primary Stage in Jordan - Mohammad Fu'ad Hawamdeh; Ayat Mohammad Abu Shhab (Deanship of Scientific Research (DSR), the University of Jordan, 2020)
The study aimed to investigate the classifications of metadiscourse and its types in the Arabic language books in the primary stage. It also aimed to uncover the level of its sequence in the Arabic language books. To achieve the objectives of the study, the researcher prepared the analysis tool and the validity of the tool and its stability were extracted. The study also adopted the sentence as a unit to analyze the books used as a sample. A set of results were discovered, the most important of which is the development of a list of classifications of the metadiscourse which includes (15) different types of classifications of the meta-discourse. The first classification is the informational metadiscourse and IT included nine types. The second classification is the attitudinal metadiscourse which included six types. The third type is the communicative meta-discourse. Results also showed that Arabic language books for the fourth, fifth, and sixth grades included (3457) incidentes of the classifications of the metadiscourse which varied in their frequency. The study also discovered that the results of classifications of the metadiscourse and their types varied. Some of those classifications were either low included or not included. Results also showed that there is no consequence nor continuity in the results of the classifications of metadiscourse in the Arabic language books of the primary stage. On the basis of these findings, the study concludes with a set of recommendations.